Pembentukan Keluarga Sakinah Pada Keluarga Jamaâah Tablig Di Kota Palangka Raya - Rahmad, Rahmad (LP2M IAIN Palangka Raya, 2015)
In this study, Â used descriptive Â avalitative Â research with the subjeck using purposive sampling. That to be a respondent is a peopleâs. A people of muslim religious teacher, and 3 peopleâs from society that is community such a religious meeting. The objeck is a formation of harmoniousÂ family in the community such a religious in Palangkaraya Raya city. The data collection, it used some techniquesÂ such as interview, Â and documentation Â . for the data validity using triangulasi and analyzing the technique are as follows : data colection, data reduction, data display and conclusion. The Â main Â research Â finding Â were: Â 1)Â the Â methodÂ to Â making Â the harmonious family must be loving, to know and function in a family, know basic right and obligation in family. In a family must to ask and more than read a book about marriage, always to communication, to believe and understanding disvantages and advantages in family and always discussion. If a aplly can their be harmonious family. 2) All of agrrement their is no the problem to Â making Â the harmonious Â family. Â 3)Â The Â method Â to Â making Â the harmonious family is a ablution, reading Alquran or reading a Yasin, trust in.